Assessing the business development strategy: a case study at an oil and gas company in Malaysia / Syed Jamal Abdul Nasir Syed Mohamad … [et al.] - Syed Mohamad, Syed Jamal Abdul Nasir; Osman, Muhamad Zulkiflee; Kamarudin, Asmawati; Mohd Arshad, Arlina Nadia; Rahim, Norliana (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
This paper discusses the greatest challenge facing a pipeline inspection company, SEGA (not the real name) in Malaysia in providing its services to the oil and gas operators based on current practices, protocols and standards. However, the most important issue for SEGA as “new kid on the block” is how it must adopt new business development strategic directions to remain relevant, viable and profitable in the future. This further argues for greater investment in technology, people development and probably going outside of its territory that will enable a long-term drift towards zero tolerance on quality and greater extraction of local skilled field crew. Now, its strategic partners with GE on IP technology and TPS as the marketing arms thriving them to the next level of growth in order to sustain its business continuity and to become a prominent pipeline inspection company in Malaysia as well as in international markets in future.